Near-Surface Air Temperature Dependence on Elevation and Geographical Coordinates Over Tropical Desert Land Surfaces - Kattel, Dambaru Ballab; Salih, Haitham Aabdin Mohamed; Yao, Tandong; Ullah, Kalim (Frontiers in Earth Science, 2022)
This study examined 30- years of in situ observations (1981-2010) to determine monthly, and diurnal characteristics of near-surface temperature gradients (TG) in the Sudanese desert, both spatially and with elevation. The TG variation, along with its spatial and elevation dependence, forcing mechanisms for its variability, and its relationship with moisture and gradients of other climatic variables, were evaluated using a multi-collinearity approach and empirical analysis, respectively. A distinct annual cycle was observed in both the temperature gradient (or lapse rate) with elevation (TGE) and the temperature gradient with latitude (TGLat). The TGE is strongly negative during the warmer months (summer) and less strongly negative (or even positive) during the colder months (winter). However, for TGLat, the results are reversed. The mean TGE value steepens during the summer due to intense adiabatic cooling during the day and less inversion during the night, while this process is reversed for the observed shallower TGLat value in the same season. This result is attributed to desert characteristics at the northern lower elevations or higher latitudes, as well as the effects of the ITCZ, moisture, and cloud cover as a result of high elevations at lower latitudes in the south and southwest region. Low solar insolation, and Mediterranean cold airflow and littoral effect, combined with inversion and radiative cooling at lower elevations or northern higher latitudes, lead the TGE (TGLat) value to be shallow (steep) during the drier months. Excluding the inversion and radiative cooling at night, this effect is more pronounced in the winter. The extreme high and low values of TGE and TGLat, as well as their diurnal range, were found to strongly coincide with variations in the equatorial trough, as well as diurnal radiative energy differences and the regional synoptic phenomenon. In addition to being valuable for hydro-climatic, ecological, and agricultural modeling, this study can be replicated in other tropical desert areas around the world to gain a better understanding of desert’s climate.